(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
This article discusses the events that contributed to the development of Behavior Analysis in Brazil and that influenced the experimental teaching of this science. It points out about the experimental models used in the context of the teaching laboratory, and about the search for alternatives to the traditional teaching in the animal laboratory and its historical determinants. Finally, it highlights the importance and urgency of developing alternative practices in the teaching laboratory.